Development and validation of a new and rapid HPLC for determination of lyophilized teicoplanin - Passoni, Mariana Henrique [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Royal Soc Chemistry, 2012)
A sensitive, precise and specific high performance liquid chromatographic method was developed for the assay of teicoplanin in injectable pharmaceutical form. Analytical parameters were studied according to the International Conference on Harmonization (ICH). The method validation parameters yielded good results and included the range, linearity, precision, accuracy, specificity and recovery. The HPLC separation was carried out by reversed phase chromatography on a Waters symmetry C-18 column (250 x 4.6 mm id, 5 mu m particle size) with a phase composed of acetonitrile : methanol (50 : 50, v/v), pumped isocratically at a flow rate of 1.0 mL min(-1). The effluent was monitored at 279 nm. The developed HPLC method to determine lyophilized teicoplanin can be used to evaluate the quality of regular production samples.